Tissue Contamination During Transportation of Formalin-Fixed, Paraffin-Embedded Blocks. Issue 1 (23rd February 2022) - Carll, Timothy; Fuja, Christine; Antic, Tatjana; Lastra, Ricardo; Pytel, Peter
Abstract: Objectives: Tissue carryovers are contaminants of surgical pathology cases in which extraneous tissue is incorporated into tissue blocks. Carryovers occur most frequently at the grossing or embedding stations, but little is published about them. We sought to analyze their transmission during transit to the histology lab. Methods: Cassettes of friable donor tissue were mixed with cassettes of spongy recipient tissue in formalin-filled containers and agitated by shipment via pneumatic tube. The tissue cassettes were processed, embedded as blocks, and cut as usual. Liquid samples were prepared from the submission containers as well as from workstation submission containers and histology tissue processor waste. Results: A high rate of contamination (14.9%) was observed under these artificial conditions. Friable donor tissue, including urothelium and colorectal adenocarcinoma, were promiscuous contaminants, as were placental villi. Fluid from submission containers showed viable tumor cells and fragments, which were also present in workstation submission containers and in tissue processor waste fluid. Conclusions: This study implicates liquid transport media as a possible avenue of contamination during submission and transportation of tissue cassettes for histologic processing. Attention should be given to the friability of submitted tissue and physical agitation of the cassettes in transit. Such contaminants may be present in the fluid in tissue submission bins and in tissue processor fluid.